2011
DOI: 10.1111/j.1477-9730.2011.00631.x
|View full text |Cite
|
Sign up to set email alerts
|

TLS data denoising by range image processing

Abstract: The work described in this paper deals with denoising of fine detail in terrestrial laser scanner (TLS) data for close‐range applications. In contrast to other denoising methods described in the literature, the method described here puts the problem back into two dimensions. In the proposed method, data from each instrument station is processed by denoising the range image as a 2D function. Then, after denoising, the registration process is applied to obtain the final 3D point cloud. Two image denoising method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…As proved in some recent studies (Bitenc et al, 2015a;Khoshelham et al, 2011;Smigiel et al, 2013Smigiel et al, , 2011Smigiel et al, , 2008 range error can be successfully reduced by image denoising methods. The TLS denoised surfaces show details, which may otherwise be lost in noise.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…As proved in some recent studies (Bitenc et al, 2015a;Khoshelham et al, 2011;Smigiel et al, 2013Smigiel et al, , 2011Smigiel et al, , 2008 range error can be successfully reduced by image denoising methods. The TLS denoised surfaces show details, which may otherwise be lost in noise.…”
Section: Introductionmentioning
confidence: 82%
“…Once the complexity of a 3D randomly scattered point cloud is reduced by gridding to a regular 2.5D surface, a wide range of existing image processing algorithms can be used. An overview of image denoising methods and further references can be found in (Buades et al, 2005;Smigiel et al, 2011;Zhang et al 2014). In this research the two methods (DWT and NLM), together with their two variants, are tested for a reliable roughness estimation.…”
Section: Denoising Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have first investigated the wavelet approach. We have then showed that the NL-means approach is much simpler to implement and more efficient as well (Smigiel et al, 2011). In this paragraph, we show very initial results of denoising based on dcitionary learning of sparse coding.…”
Section: Range Image Denoising By Dictionary Learning Of Sparse Codingmentioning
confidence: 99%
“…An advantage of 2.5D surface is that a whole range of existing image processing algorithms can be used. An overview of image denoising methods and further references can be found in (Buades et al, 2005;Smigiel et al, 2011;Zhang et al 2014). …”
Section: Introductionmentioning
confidence: 99%